2020
DOI: 10.3390/ijerph17072485
|View full text |Cite
|
Sign up to set email alerts
|

Humor Styles as New Resources in a Primary Preventive Perspective: Reducing Resistance to Change for Negotiation

Abstract: Reducing resistance to change is fundamental to dealing with the rapid and continuous changes of the 21st century labor market. Personality traits have been widely studied in relation to resistance to change. However, personality is not completely suitable for primary prevention intervention, since it does not change over time. Instead, humor styles appear to be a promising preventive resource to facilitate the negotiation process by enabling individuals to cope with the current work environment. Using a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Overwhelming stress developed from this process is the only way to proceed from deeply rooted patterns to a new context (Gorospe and Edaniol, 2022). Di Fabio and Duradoni (2020) explained that psychological capital might affect employee acceptance or resistance to change in the workplace. As a result, new working methods and the supply of contributions to employees with the required motivation are implemented (Jiony et al, 2021).…”
Section: Psychological Capital and Resistance To Changementioning
confidence: 99%
See 1 more Smart Citation
“…Overwhelming stress developed from this process is the only way to proceed from deeply rooted patterns to a new context (Gorospe and Edaniol, 2022). Di Fabio and Duradoni (2020) explained that psychological capital might affect employee acceptance or resistance to change in the workplace. As a result, new working methods and the supply of contributions to employees with the required motivation are implemented (Jiony et al, 2021).…”
Section: Psychological Capital and Resistance To Changementioning
confidence: 99%
“…According to Di Fabio and Duradoni (2020), human resources combined with organizational techniques in the workplace have a positive impact on organizational outcomes. A different kind of capital, according to Goleman (2017), is psychological capital.…”
Section: Emotional Intelligence: the Moderating Rolementioning
confidence: 99%
“…The HSQ (Martin et al, 2003); Italian version (Di Fabio, 2019) is a self-report scale encompassing 32 items rated on a seven-point Likert-type scale (from 1 = totally disagree to 7 = totally agree). The questionnaire rates four humor styles: affiliative humor (example of item “I enjoy making people laugh”), self-enhancing humor (example of item “It is my experience that thinking about some amusing aspect of a situation is often a very effective way of coping with problems”), aggressive humor (example of item “If I don’t like someone, I often use humor or teasing to put them down”), self-defeating humor (example of item “I let people laugh at me or make fun at my expense more than I should”).…”
Section: Methodsmentioning
confidence: 99%
“…Primary prevention is an early intervention that starts before the occurrence of problems ( Caplan, 1964 ). It is centered on the building of the strengths of workers enhancing positive individual resources such as emotional intelligence ( Di Fabio and Saklofske, 2014 ; Di Fabio, 2015 ), resilience ( Di Fabio and Kenny, 2015 ; Wilson et al, 2017 ), and humor styles ( Di Fabio and Duradoni, 2020 ). The focus on building resources and strengths ( Di Fabio and Saklofske, 2021 ) in a primary preventive framework ( Di Fabio and Kenny, 2016 ; Di Fabio et al, 2017 ), namely positive strength-based primary preventive, could be a promising approach for vulnerable workers.…”
Section: Enriching the Positive Perspective For Marginalized And Vulnerable Workers: Positive Healthy Organizations And Strength-based Prmentioning
confidence: 99%
“…An increasing number of studies have shown primary preventive approaches in the domain of sustainable sciences (e.g., Leporelli and Santi, 2019 ; Santi et al, 2019 ; Chotchoungchatchai et al, 2020 ; Nowacki et al, 2020 ), and scholars have advanced these interventions to foster the strengths of the employees (e.g., Di Fabio, 2019 ; Di Fabio and Duradoni, 2019 , 2020 ). However, future studies are needed to expand knowledge on positive strength-based primary preventive interventions in vulnerable workers.…”
Section: Enriching the Positive Perspective For Marginalized And Vulnerable Workers: Positive Healthy Organizations And Strength-based Prmentioning
confidence: 99%